The Effect Of Implementing Richpeace Software On The Competency Of Clothing Pattern Making In Semester III PKK Students, Centration In Clothing Design, USK - Sarah Nadia; Rahmi (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to determine : (1) the differences competency between students taught with Richpeace Software and students taught without applying Richpeace Software in making fashion patterns for Semester III PKK students with Fashion Design concentration; (2) The application of Richpeace Software has an effect on the competency of making fashion patterns for Semester III PKK students with Fashion Design concentration. Type of research used Quasi Experimental Research with NonRandomized Control-Group Pretest-Posttest Design model . Research conducted on Semester III PKK students , Fashion Design Concentration , Syiah Kuala University. The results of the study show that : (1) there is difference results Study between students who study with implementing Richpeace Software with students who study without implementing Richpeace Software in making fashion pattern with mark probability or significant 0.000 < 0.05, so H0 is rejected and H1 is accepted ; 2) the existence of influence in Richpeace Software Implementation to competence making fashion patterns , this is proven with mark probability or significance is 0.000<0.05, then H0 is rejected and H1 is accepted . The response results student to Software implementation Richpiece show 58.33 % agreed and 33.33% strongly agreed , meaning student give positive response​ to learning in the Basic Fashion Course . Furthermore , the application of Richpeace Software can made into alternative in learning in the Basic Fashion Course , because making pattern with digital way can increase competence student in meet the world of work in accordance with the 21st century era .